2004
DOI: 10.1158/0008-5472.can-03-2594
|View full text |Cite
|
Sign up to set email alerts
|

Selective Usage of D-Type Cyclins by Ewing’s Tumors and Rhabdomyosarcomas

Abstract: The genetic mechanisms that control proliferation of childhood musculoskeletal malignancies, notably Ewing's tumor (ET) and rhabdomyosarcoma (RMS), remain largely unknown. Most human cancers appear to overexpress at least one of the G 1 cyclins (cyclins D1, D2, D3, E1, and E2) to bypass normal regulation of cell cycle G 1 progression. We compared the gene expression profiles of 7 ET and 13 RMS primary tumor samples and found overexpression of cyclin D1 in all 7 ET samples. In contrast, RMS samples expressed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 55 publications
2
49
1
1
Order By: Relevance
“…Also, a recent study has demonstrated distinct regulation of D-type cyclins in Ewing tumor cells; in TC-71 Ewing sarcoma cells, inhibition of EWSFli1 decreases the level of cyclin D1 but increases that of cyclin D3 (43). However, in TC-135 cells, we showed that cyclin D3 expression was down-regulated by transfection with EWS-Fli1 siRNA.…”
Section: The Relationship Between Ews-fli1 and Pld Expression In Cellcontrasting
confidence: 51%
See 2 more Smart Citations
“…Also, a recent study has demonstrated distinct regulation of D-type cyclins in Ewing tumor cells; in TC-71 Ewing sarcoma cells, inhibition of EWSFli1 decreases the level of cyclin D1 but increases that of cyclin D3 (43). However, in TC-135 cells, we showed that cyclin D3 expression was down-regulated by transfection with EWS-Fli1 siRNA.…”
Section: The Relationship Between Ews-fli1 and Pld Expression In Cellcontrasting
confidence: 51%
“…The Effect of cyclin D Expression on Ewing Sarcoma CellsSome previous studies have shown that EWS-Fli1 is correlated with cyclin D expression (43)(44)(45)(46). Also, a recent study has demonstrated distinct regulation of D-type cyclins in Ewing tumor cells; in TC-71 Ewing sarcoma cells, inhibition of EWSFli1 decreases the level of cyclin D1 but increases that of cyclin D3 (43).…”
Section: The Relationship Between Ews-fli1 and Pld Expression In Cellmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, as mentioned above, forced expression of RAGE in TE671 cells results in down-regulation of expression of cyclin D1 ( Figure 5I), which is overexpressed in highly proliferating, metastatic cells, including RMS cells, has an important role in cellular survival and DNA synthesis, and is induced by sustained activation of ERK1/2. [62][63][64][65][66] Our data suggest that RAGE signaling in TE671/RAGE cells might down-regulate the expression of cyclin D1 via p38 MAPK-dependent inhibition of ERK1/2 and JNK activities. 28,67 After the submission of the present work, data have appeared showing that p38 MAPK causes myoblast proliferation arrest by inactivating JNK via up-regulation of MAPK phosphatase-1.…”
Section: Discussionmentioning
confidence: 91%
“…Reduction of EWS/FLI-1 expression decreases EFT cell growth in vitro and tumor-forming capacity in vivo, showing that these oncoproteins maintain cellular proliferation and survival (Tanaka et al, 1997;Prieur et al, 2004;Hu-Lieskovan et al, 2005a). Accordingly EWS/ETS proteins regulate expression from the proliferation-associated MYC, CCND1, TGFBR2, CDKN1A and p57KIP genes (Bailly et al, 1994;Hahm et al, 1999;Dauphinot et al, 2001;Nakatani et al, 2003;Zhang et al, 2004). EWS/ETS proteins also regulate differentiation of a variety of cell types (Eliazer et al, 2003;Torchia et al, 2003;Rorie et al, 2004;Riggi et al, 2005;Hu-Lieskovan et al, 2005b;Yeny et al, 2005).…”
Section: Introductionmentioning
confidence: 99%